Digital Academic Engagement: Educational realities in permanent transformation: Engagement Acadêmico Digital: Realidades educativas em permanente transformação (Papeles, 2024)
Introduction: This study synthesizes data from an exploratory research of a qualitative nature that sought to investigate: ¿How did digital resources contribute to the promotion of a process of digital academic engagement? Methodologically, we opted for a narrative literature review (bibliographic review), whose alternative aimed to know and discuss the development of the theme chosen and analyzed, from a theoretical and contextual point of view, but without exhausting the quantity produced. Results and discussions: The results showed, in different ways, the contribution of digital technologies to the promotion of digital academic engagement, especially in times of the Covid-19 pandemic; The use of different digital connection alternatives was the only alternative considered safe during the pandemic period, as it enabled students to learn and (re)learn, supported and connected to their teachers and peers; the recurrent transformations involving digital technologies demand digital teachers, with specific skills to put technology at the service of the pedagogical model and introduce it in the classroom, to improve the quality of teaching; technologies favor the promotion of a gradual digital academic engagement process in an upward spiral. Conclusions: Digital academic engagement offers immense possibilities for the equitable and inclusive development of skills and abilities, access and sharing of different worldviews at any time and place, thus enhancing different teaching and learning processes.
Keywords: Engagement; Digital Technologies; University education